Assessment of lifestyle among e-rickshaw drivers in Delhi using the simple lifestyle indicator questionnaire: a community-based cross-sectional study - Trilok, Sahil; Sharma, Rahul; Chhabra , Pragti (International Journal Of Community Medicine And Public Health, 2026)
Background: E-rickshaw drivers are an important component of the urban informal workforce and are exposed to several occupational and lifestyle-related risk factors. This study was conducted to assess the lifestyle of e-rickshaw drivers in Delhi and its association with selected socio-demographic characteristics. Methods: A community-based cross-sectional study was conducted among 254 e-rickshaw drivers operating in selected municipal zones of Delhi. Lifestyle was assessed using the simple lifestyle indicator questionnaire (SLIQ). Data were analysed using descriptive statistics, and associations between lifestyle and selected socio-demographic characteristics were assessed using the Chi-square test and Fisher’s exact test, with statistical significance set at p<0.05. Results: Overall, 50.8% of the participants had an unhealthy lifestyle, while 49.2% had a healthy lifestyle according to the simple lifestyle indicator questionnaire (SLIQ). Good/poor lifestyle was significantly associated with (younger/advanced) age (p=0.001), (higher/lower) educational status (p=0.010), and number of family members (how many) (p=0.011), whereas no statistically significant association was observed with socioeconomic status (p=0.271). Conclusions: The findings highlight the pressing need for targeted public health interventions aimed at promoting healthier lifestyles among e-rickshaw drivers (by doing what?). Future longitudinal studies are warranted to better understand causal relationships and to better inform evidence-based public health strategies.